Orbital Prosthetic Rehabilitation in “ADAM Complex” Multiple Orofacial-Cleft Disruption Syndrome - Aparna Barabde; Shailesh M. Barabde; Ashish Bhagat; Amar Thakare (Case Reports in Surgery)
To be human is great; to look human is wonderful! It is nature's greatest gift! Mother nature's womb is the safest place on earth for any life, but the calamity strikes and no one knows how Hence, Treasure your exceptions!, since nature seems nowhere accustomed more openly to display, its secret mysteries than in cases where it shows traces of its workings apart from the beaten path. A dismorphological pattern of congenital oro-craniofacial and limb defects which is a rare form of amniotic rupture sequence required persistent coordinated efforts of multiple disciplines and had manifested as bizarre orofacial clefting, cat eye syndrome with an ectopic eye, and aberrant tissue band lesions on limb. The challenge was to meet the child’s clamour for functional demands on premature exposure to open world and was overcome through a phased treatment implementation. Anophthalmos resulting from multiple ophthalmic surgeries for aberrant ectopic left eye and cat eye syndrome of right eye required a staged sequential preemptive planning for a successful outcome. Every phase of fabrication of orbital prosthesis comes with an impending challenge. Thus, a well-defined technique eliminating the common errors and creating a natural looking prosthesis, in the face of limitations, is imperative.